2015
DOI: 10.13075/ijomeh.1896.00316
|View full text |Cite
|
Sign up to set email alerts
|

Maternal waterpipe smoke exposure and the risk of asthma and allergic diseases in childhood: A post hoc analysis

Abstract: Objectives: This analysis was conducted with the objective of evaluating association between waterpipe passive smoking exposure and asthma, and allergies among Lebanese children. Material and Methods: Data were taken from a crosssectional study on children from public and private schools. A sample of 22 schools participated in the study, where standardized written core questionnaires were distributed. From 5 to 12-year-old students filled in the questionnaires at home, while 13-14-year-old students filled it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
6
15
1
Order By: Relevance
“…We also found a significant association between the positive family history for allergies and current asthma in children, which is consistent with the results of other studies . Study results examining asthma family risk have been inconclusive with some pointing to a maternal link, others to a paternal link, and others have not found an association between asthma and family history .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found a significant association between the positive family history for allergies and current asthma in children, which is consistent with the results of other studies . Study results examining asthma family risk have been inconclusive with some pointing to a maternal link, others to a paternal link, and others have not found an association between asthma and family history .…”
Section: Discussionsupporting
confidence: 92%
“…Our study findings showed that males are at a higher risk for current asthma than females, which is similar to what is described in the literature, although the exact mechanisms for sex‐related differences in asthma have not been fully determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that male sex, a well-known risk factor in the literature [32], might be associated with an increase in asthma symptoms during the last 12 months (multivariate analysis). Unlike our results, which showed no association, some epidemiological studies suggest that low monthly family income and area of residence were positively associated with rhinoconjunctivitis symptoms [33,34,41]. In addition, our findings are in line with some epidemiological studies on risk factors for allergic diseases, which noted that the history of familial allergy [32] and postnatal respiratory complications [42] might be positively associated with the onset of symptoms of asthma and rhinoconjunctivitis during the past 12 months.…”
Section: Ora [95% Ic] P-valuesupporting
confidence: 85%
“…As for Lebanon, no studies identified the association between dietary factors and allergic diseases in children and particularly public schools students. However, there are published studies on the prevalence and severity of atopic conditions in Lebanon among students of private schools and their risk factors, such as the studies by Waked et al [32][33][34][35]. This study attempts to evaluate the association between dietary factors and the symptoms of allergic diseases in children aged 8 to 12 in public schools in Beirut and Mount Lebanon.…”
Section: Introductionmentioning
confidence: 99%